Answer:
Equation of parabola is :
![f(x) = 4x^2 + 3x -6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zsf6jddjn4ih3xtom6br8ppa9ijsdpcouk.png)
Explanation:
Given,
x = -2 0 4
f(x) = 4 -6 70
General equation of parabola is:
![y = ax^2 + bx + c](https://img.qammunity.org/2020/formulas/mathematics/middle-school/72htg4ztysqasql8ylcgfcrnpg7c3ci0gd.png)
Now we plug corresponding x and y values to get coefficient a,b and c.
Fro x =-2 and y( =f(x) ) = 4
______(1)
For x = 0 , y = -6
_____(2)
For x = 4 , y = 70
_____(3)
Plug c= - 6 in equation (1) and (3)
We get,
![4 = 4a - 2b - 6 \\And\\70 = 16a + 4b - 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ucas9b1dazwiktd7dykazes9tnguw75ikv.png)
solving above two equations to find a and b.
Multiply equation (1) by 2 then add equation (1) and (3)
![8 + 70 = 8a + 16a -4b + 4b -12 -6\\78 = 24a - 18\\78 + 18 = 24a\\a = 96/24 = 4\\And b = 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zoijhbutry62f39c8b3tzzgwf1ak0w72dw.png)
Hence equation of parabola is :
![f(x) = 4x^2 + 3x -6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zsf6jddjn4ih3xtom6br8ppa9ijsdpcouk.png)